Anthropocentric Symbols in Where the Wild Things Are by Maurice Sendak - Regga Navratilova Ariyanto; Rahayu Puji Haryanti (Universitas Islam Negeri Palopo, 2025)
The purpose of this study is to analyze the anthropocentric symbols present in the children's storybook